Impacts and adaptation extents of climate smart agricultural practices among smallholder farmers of Ethiopia: Implication to food and nutrition security - Beyan Ahmed; Jema Haji; Mengistu Ketema; Kedir Jemal (Cogent Economics & Finance, 2023)
The integrated use of various levels of climate change adaptation practices is a means of increasing farm productivity to meet the food demand of the world's growing population without harming the environment. Both primary and secondary data were used. In the 2020/21 production year, primary data was collected from 461 sample households of East Hararghe Zone, Oromia, Ethiopia, for the study. For data analysis, the study employed descriptive statistics and multinomial endogenous switching econometric model. Gender, education, extension, livestock holding, cooperatives, market information, soil fertility, farm land slopes, training on land management, climate change information, training, perception of land degradation, climate change perception, and weather road distance are estimated to have a significant influence on the probability of adopting different levels of climate smart practices. According to the impact evaluation results, adopting low levels of climate smart practices increases households' food and nutrition security by 28% and 4.3%, respectively. Adopting medium-level climate-smart practices boosts food and nutrition security by 43% and 20%, respectively. Adopting high and higher levels of climate smart practices increases food and nutrition security by 56% and 19%, respectively, over very low adopter households. As a result, policymakers should place a premium on climate change adaptation agricultural practices in order to improve rural households' livelihoods.
Keywords: 330; Ethiopia; Extents of adoption; food and nutrition and Multinomial endogenous switching